Politeness in Using Mandailingnese Personal Subject Pronouns in Medan - Tanjung, Surya Ningsih; Mayasari, Mayasari (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
A bstract -- This research aim s to explain and reveal Politeness in Using Ma n da i l i n g ne s e Personal Subject Pronouns by trying to find out of the type s , the way and the reason of used mandailingnese personal subject pronouns mostly by people in Medan around L in g k un g an K e l u r ah an Ba n tan T i mu r. The theory of this research used Leech (2014) Brown&Levinson (1987) theory. This research took 25 respondent and conducted quantitatively. The data was collected by using questionnaire that distributed to different people. The finding of this research shows that Mandailingnese Personal Subject Pronouns are mostly used by people live at Lingkungan Kelurahan Bantan Timur. The First Personal Subject Pronouns Au/Ku with 89 times chosen (51%), Second Personal Subject Pronouns Ho/Hamu/Amu with 118 times chosen (67%), Third Personal Subject Pronouns Ia/Halai with 115 times chosen (65%). The reason why people live at Lingkungan Kelurahan Bantan Timur use Mandailingnese Personal Subject Pronouns are determine by gender, situation, age and familiarity. The reason of people using Mandailingnese Personal Subject Pronouns were making no distance/gap, adapting the situation, knowing the rules of communication and learning from family also the findings of this research revealed that four parameters of politeness influenced chosen of pronouns, and the use of the pronouns of Mandailing People itself influenced the level of politeness .   Keywords : Socio-Pragmatics; Politeness;, M andailingnese; Personal Subject Prono